Squamous Cell Carcinoma Arising on Mature Cystic Teratoma: A Case Report - Nazrin, Mosammat Suchana; Chowdhury, Shafiqul Haque; Shah, Md. Ar-Rafi Ali (Journal of Current and Advance Medical Research, 2025)
Mature cystic teratoma is the common ovarian tumor in women of reproductive age. The malignant transformation of mature cystic teratomas is a rare entity. The most common malignant tumor in mature cystic teratomas is squamous cell carcinoma, A 50 years old postmenopasual women, admitted in a private hospital, Sylhet, Bangladesh with the complaints of feeling of lump in the abdomen for the past 3-4 months, associated with abdominal pain for one week and occasional constipation. The patient was diagnosed clinically as a case of ovarian tumor. CT findings were consistent with dermoid cyst. The patient underwent Total Hysterectomy with Bilateral Salpingo-Oophorectomy (TH with BSO). Histopathological examination confirmed the diagnosis of squamous cell carcinoma arising on mature cystic teratoma. Journal of Current and Advance Medical Research, July 2024;11(2):123-125